TO COMPARE MATERNAL AND FETAL OUTCOME IN OBESE VERSES NON-OBESE LABORING MOTHERS - Saher Fatima; Anjum Rehman (Journal of University Medical & Dental College, 1970)
ABSTRACT Objective: To compare maternal and fetal outcome in obese verses non-obese laboring mothers. Study Design: Case Control Comparative. Place and duration: January 2009 to October 2010. Subjects and Methods: We Selected 100 obese versus non-obese women who presented to us in labor and the data was collected regarding maternal and fetal complication noted during intrapartum and postpartum period till the patient was discharged from the hospital. Result: The age range of our patients was between 18-37 years with a mean age of 26.4 years. Twenty four percent presented postdate while 9% were post-term among obese patients. Twenty nine percent of obese needed induction while only 12% among non-obese needed induction. Thirty six percent of obese compared to 10% of non-obese needed C-Section. Shoulder dystocia occurred in 8% of obese while only 1% in non-obese. Postpartum hemorrhage occurred in 45% and 11% in obese and non-obese respectively. Macrocosmia was encountered in 26% of obese versus 4% non-obese. Stillbirth was observed in 9% of the patient belonging to obese group. Conclusion: This study proves that maternal obesity is associated with adverse fetal and maternal outcomes in pregnancy including prolonged pregnancy, failed induction, operative deliveries, perineal tears, postpartum hemorrhage and postpartum infections. So these women should be considered and treated as high risk pregnancies.